Internalisasi Nilai-Nilai Kepemimpinan Profetik Dalam Lembaga Pendidikan Islam - Muhammad Fadhli (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
Leadership is a key factor in the success of Islamic education institutions to achieve the desired quality. Leadership can be define and interpreted as a process of influencing other people to be involved and to bring change to the desired future. Some theories and models of leadership have existed so far and become the main reference in Islamic education institutions. But it has not been able to make Islamic education institutions a quality educational institution. There are still many people who think that Islamic education institutions are second-class educational institutions. Prophetic leadership is one of the comprehensive leadership models because it is taken directly from the style, method, type carried out by the Prophets. The internalization of the value of prophetic leadership allowsIslamic education leaders to be better because in the process of leadership adhering to the Qur’an and hadith.